1976
DOI: 10.1071/ar9760881
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of cereal stubbles for sheep production

Abstract: The production of young crossbred wethers grazing oat, barley and wheat stubbles was measured in each of three years at stocking rates ranging from 15 to 30/ha. In one year, production on 'weedy' stubbles was compared with that of 'clean' (weed-free) stubbles, and also the effect of a wheat–urea–mineral supplement on the production of sheep was measured on oat stubble. Liveweight change and wool production were significantly influenced by the availability of green plant material and by stocking rate, but not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 0 publications
0
10
1
Order By: Relevance
“…7). Nitrogen concentration of stubbles measured in our survey was 20-25% lower than has been reported in previous studies (Mulholland et al 1976;Roberts and Paterson 2001). These results suggest there are Genetics • Environment • Management (G • E • M) factors in modern crop production that have resulted in decreases in the nutritive value of stubbles, that are independent of any changes in the amount of unharvested grains or weeds.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…7). Nitrogen concentration of stubbles measured in our survey was 20-25% lower than has been reported in previous studies (Mulholland et al 1976;Roberts and Paterson 2001). These results suggest there are Genetics • Environment • Management (G • E • M) factors in modern crop production that have resulted in decreases in the nutritive value of stubbles, that are independent of any changes in the amount of unharvested grains or weeds.…”
Section: Discussioncontrasting
confidence: 68%
“…Anecdotally, farmers consider barley stubbles to be of higher value than wheat stubbles, but whether this is due to higher levels of grain, the higher-quality stubble components, differences in the capacity of animals to select their preferred diet, or a combination of all these, is not known. Sheep actively select green pick in stubbles when it is available, Mulholland et al (1976) found that sheep diets were over 80% green material where green biomass was higher than 40 kg/ha. While predicting the feeding value of stubbles remains a challenge, the skilful integration of research should improve the ability to manage feed budgeting with stubbles.…”
Section: Discussionmentioning
confidence: 99%
“…It does not supply sufficient nutrients to fulfil the high protein and energy needs of reproducing ewes (Aitchison, 1988;Brand et al, 2000). Owing to the low digestibility of wheat stubble, there is reduced intake (Mulholland et al, 1976), which results in a decrease in the nutrient intake by ewes. Supplementary feeding is needed for additional energy and protein (Aitchison, 1988;Brand et al, 1997a).…”
Section: Introductionmentioning
confidence: 99%
“…The feeding value of crop stubbles varies widely, and the feed intake of sheep has been reported to range from 4.4 to 9.8 MJ/sheep/day depending on the crop type, grazing intensity, and whether green summer plants have grown in the stubble [2] .…”
Section: Introductionmentioning
confidence: 99%
“…However, animal production from crop stubble is limited owing to certain nutrient de ciencies in the available material. The low productivity of animals grazing on crop stubble is also associated with low digestibility [1] and resultant low intake [2]of the available material. Crop stubble has low levels of nitrogen (N) and available carbohydrates, high cell wall content, and poor digestibility [1] , rendering it unsuitable to meet the high nutrient requirements of productive sheep [3] .…”
Section: Introductionmentioning
confidence: 99%